Sodium-potassium co-doped lithium ion battery cathode material, preparation method and application thereof
Patent Information
- Application Number
- CN202511328742.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-17
- Publication Date
- 2026-10-30
AI Technical Summary
但是单掺杂仅优化体相的单一维度,难以协同解决动力学与稳定性问题
[0011]本发明根据与
离子半径存在差异,因此可以实现”双重柱撑”和“梯度柱撑”的作用,Na+和K+可占据不同位置或形成协同支撑。K+提供强大的主支撑骨架扩大层间距,Na+在间隙和协同位置进一步优化层间结构和Li+扩散路径。这种双掺杂策略可以在不牺牲锂离子电池可逆容量和稳定结构的基础上,在相同电压下提高锂离子脱出状态,从而实现更高的容量;此外还能更有效地降低Li+扩散能垒,显著提升倍率性能;而且双掺杂策略可协同抑制混排和相变,Na+和K+共同占据锂位,形成更致密的物理屏障,比单掺更有效地协同抑制阳离子混排和有害相变,大幅提升锂离子电池的结构稳定性和长循环性能。
Smart Images

Figure CN123002912A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery technology, specifically relating to a sodium-potassium co-doped lithium-ion battery cathode material, its preparation method, and its application. Background Technology
[0002] Nickel-rich layered cathode materials (such as Li) 1-x Ni 0.83 Co 0.12 Mn 0.05 While O2 can provide high specific capacity (0.1C discharge capacity > 190 mAh / g), its high nickel content (Ni ≥ 80%) causes multiple coupling degradation problems, the root cause of which lies in the delithiated Ni. 4+ The high reactivity and anisotropic lattice contraction of Ni. At the chemical level, during the charging process... 4+ Because the low LUMO (lowest unoccupied molecular orbital) energy level is extremely unstable, on the one hand, it drives the release of lattice oxygen by enhancing the covalent nature of Ni-O bonds, triggering violent oxidative decomposition of the electrolyte when the charge exceeds 80%, generating CO2 / CO / H2O and a thick cathode electrolyte interface layer (CEI layer), thus leading to a large impedance; on the other hand, side reactions easily occur at the electrode / electrolyte interface, accelerating TM dissolution. Furthermore, as the discharge process proceeds, Ni... 4+ Reduced to Ni 2+ Because of Ni 2+ With Li + With similar ionic radii, Li / Ni readily undergoes site exchange during synthesis and cycling, leading to Li / Ni mixed-up defects. These defects not only hinder the synthesis of Li... + Migration within interlayer diffusion channels (kinetically hindered) also leads to the formation of a rock-salt phase (NiO-like) in the near-surface region, significantly increasing interfacial impedance and reducing reversible capacity. Mechanically, the H2-H3 phase transition (typically >4.2V) causes abrupt shrinkage of the c-axis lattice, resulting in anisotropic strain accumulating stress at grain boundaries, inducing intergranular microcracks and intragranular cracks. These microcracks allow electrolyte intrusion into the particle interior, exposing Ni... 4+ Accelerated bulk side reactions. Specifically, with increasing nickel content (x≥0.8), materials face three core challenges: poor cycle stability, intensified interfacial side reactions, and slow lithium-ion diffusion kinetics. First, structural degradation occurs, with the H2-H3 phase transition at high voltages (>4.3V) inducing lattice distortion and microcracks. Second, interfacial instability occurs, with residual lithium on the surface reacting with the electrolyte to generate hydrofluoric acid (HF), corroding active materials. Third, kinetic limitations exist, with large-size single-crystal particles or secondary spheres containing Li... + The solid-phase diffusion path is too long.
[0003] In existing technologies, sodium doping (Na) +It can uniformly occupy Li sites and regulate Ni 3+ Constructing high-speed Li-Teller distortion along the Jahn-Teller direction. + Diffusion channels alleviate phase transition stress; potassium doping (K + This can increase the (003) interlayer spacing (0.4746 nm), reduce cation mixing (1.87%), and improve the bulk Li... + Transport rate. However, single doping only optimizes a single dimension of the bulk phase, making it difficult to synergistically address kinetic and stability issues. Summary of the Invention
[0004] The main objective of this invention is to provide a sodium-potassium co-doped lithium-ion battery cathode material, its preparation method, and its application, so as to overcome the shortcomings of the prior art.
[0005] To achieve the aforementioned objectives, the technical solution adopted by this invention includes:
[0006] The first aspect of this invention provides a method for preparing a sodium-potassium co-doped lithium-ion battery cathode material, comprising: Ni 0.83 Mn 0.12 Co 0.05 The (OH)2 precursor was mixed evenly with the lithiation agent, and sodium and potassium salts were added as dopants. Then, the mixture was pre-calcined and calcined in an oxygen atmosphere to obtain sodium-potassium co-doped lithium-ion battery cathode material.
[0007] A second aspect of the present invention provides a sodium-potassium co-doped lithium-ion battery cathode material prepared by the aforementioned preparation method.
[0008] A third aspect of the present invention provides a lithium-ion cathode comprising the sodium-potassium co-doped lithium-ion battery cathode material.
[0009] A fourth aspect of the present invention provides a lithium-ion battery comprising a negative electrode, a positive electrode, and an electrolyte, wherein the positive electrode comprises the lithium-ion positive electrode.
[0010] Compared with the prior art, the present invention has at least the following beneficial effects:
[0011] This invention is based on and The difference in ionic radius allows for the implementation of both "double pillaring" and "gradient pillaring" effects, in Na. + and K + It can occupy different positions or form a collaborative support. K + Provides a robust main support framework to expand interlayer spacing, Na + Further optimization of interlayer structure and Li in gaps and synergistic positions. +Diffusion pathway. This dual-doping strategy can improve the lithium-ion extraction state at the same voltage without sacrificing the reversible capacity and stable structure of the lithium-ion battery, thereby achieving higher capacity; in addition, it can more effectively reduce Li-ion degradation. + The diffusion barrier significantly improves rate performance; moreover, the dual-doping strategy can synergistically suppress mixing and phase transitions, Na + and K + Together they occupy lithium sites, forming a denser physical barrier, which more effectively suppresses cation mixing and harmful phase transitions than single doping, significantly improving the structural stability and long-cycle performance of lithium-ion batteries. Attached Figure Description
[0012] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0013] Figure 1a This is a SEM image of K2Na1-NCM811 prepared in Example 1 of this invention at 30 μm.
[0014] Figure 1b This is a SEM image of K2Na1-NCM811 prepared in Example 1 of this invention at 2 μm.
[0015] Figure 2a This is a SEM image of K1Na2-NCM811 obtained in Example 2 of this invention at 30 μm.
[0016] Figure 2b This is a SEM image of K1Na2-NCM811 obtained in Example 2 of this invention at 2 μm.
[0017] Figure 3a This is a SEM image of K3Na0-NCM811 prepared in Comparative Example 1 of this invention at 30 μm.
[0018] Figure 3b This is a SEM image of K3Na0-NCM811 prepared in Comparative Example 1 of this invention at 2 μm.
[0019] Figure 4a This is a SEM image of P-NCM811 prepared in Comparative Example 2 of this invention at 30 μm.
[0020] Figure 4b This is a SEM image of P-NCM811 prepared in Comparative Example 2 of this invention at 2 μm.
[0021] Figure 5 This is a comparison chart of the rate performance of the samples prepared in Examples 1-2 and Comparative Examples 1-2 of this invention under different doping ratios of sodium and potassium.
[0022] Figure 6 These are the performance graphs of the samples prepared in Examples 1-2 and Comparative Examples 1-2 of this invention at 1C rate for 170 cycles under different doping ratios of sodium and potassium.
[0023] Figure 7 These are the performance graphs of the samples prepared in Examples 1-2 and Comparative Examples 1-2 of this invention at 5C rate for 200 cycles under different doping ratios of sodium and potassium.
[0024] Figure 8 This is a comparison of the first-cycle cyclic voltammetry (CV) of the samples prepared in Examples 1-2 and Comparative Examples 1-2 of the present invention under different doping ratios of sodium and potassium.
[0025] Figure 9 These are test images of samples prepared in Examples 1-2 and Comparative Examples 1-2 of this invention under different sodium and potassium doping ratios using the galvanostatic intermittent titration (GITT) technique.
[0026] Figure 10 These are XRD characterization diagrams of the samples obtained in Examples 1-2 and Comparative Examples 1-2 of this invention. Detailed Implementation
[0027] In view of the problems existing in the prior art, the inventors of this invention, through extensive and in-depth research, provide a sodium-potassium co-doped lithium-ion battery cathode material, its preparation method, and its application, which mainly uses K + Na + A synergistic co-doping strategy was employed to prepare high-performance polycrystalline nickel-rich nickel-cobalt-manganese ternary (NCM-NK) cathode materials.
[0028] The following will provide a further explanation of the technical solution, its implementation process, and its principles.
[0029] The first aspect of this invention provides a method for preparing a sodium-potassium co-doped lithium-ion battery cathode material, comprising: Ni 0.83 Mn 0.12 Co 0.05 The (OH)2 precursor was mixed evenly with the lithiation agent, and sodium and potassium salts were added as dopants. Then, the mixture was pre-calcined and calcined in an oxygen atmosphere to obtain sodium-potassium co-doped lithium-ion battery cathode material.
[0030] In some embodiments, the preparation method specifically includes: pre-calcining at 480-560℃ for 2-4 hours, followed by calcination at 780-810℃ for 10-14 hours to obtain the sodium-potassium co-doped lithium-ion battery cathode material.
[0031] In some preferred embodiments, the preparation method specifically includes: pre-calcining at 560°C for 2 hours, followed by calcination at 800°C for 12 hours, to obtain the sodium-potassium co-doped lithium-ion battery cathode material.
[0032] In some embodiments, the molar ratio of sodium in the sodium salt to potassium in the potassium salt is 1:2 to 2:1.
[0033] In some implementations, the Ni 0.83 Mn 0.12 Co 0.05 The molar ratio of (OH)2 precursor to LiOH·H2O is 1:1.04 to 1.06.
[0034] In some preferred embodiments, the Ni 0.83 Mn 0.12 Co 0.05 The molar ratio of (OH)2 precursor to LiOH·H2O is 1:1.05.
[0035] In some implementations, the Ni 0.83 Mn 0.12 Co 0.05 The molar ratio of (OH)2 precursor to dopant is 1:0.003.
[0036] In some implementations, the Ni 0.83 Mn 0.12 Co 0.05 The (OH)2 precursor was prepared by a ternary coprecipitation method.
[0037] In some embodiments, the lithiating agent includes LiOH·H2O, but is not limited to this.
[0038] In some embodiments, the sodium salt includes CH3COONa·H2O, but is not limited to this.
[0039] In some embodiments, the potassium salt includes KNO3, but is not limited to this.
[0040] In some more specific embodiments, the preparation method of the sodium-potassium co-doped lithium-ion battery cathode material specifically includes the following steps:
[0041] Ni 0.83 Mn 0.12 Co 0.05(OH)2 and a lithiating agent are mixed at a molar ratio of 1:1.05, and CH3COONa·H2O and KNO3 are added as dopants, wherein the molar ratio of Na to K is 1:2 to 2:1. After the mixture is thoroughly ground and homogenized, it is placed in an alumina crucible and heat-treated in a tube furnace under an oxygen atmosphere. First, it is pre-calcined at 480 to 560°C for 2 to 4 hours, and then calcined at 780 to 810°C for 10 to 14 hours. It is then naturally cooled to room temperature with the furnace to obtain the sodium-potassium co-doped lithium-ion battery cathode material.
[0042] The innovation of this invention lies in leveraging the ionic radius differences between lithium, sodium, and potassium ions to create a "double pillar" and "gradient support" in the lithium layer, thereby seeking to address the Na+ ionization problem. + and K + The synergistic effect of sodium-potassium co-doping in this invention addresses two key bottlenecks: lithium-ion diffusion kinetics and structural stability in materials. This invention's sodium-potassium co-doping strategy can improve the lithium-ion extraction state at the same voltage without sacrificing the reversible capacity and stable structure of lithium-ion batteries, thereby achieving higher capacity.
[0043] The second aspect of the present invention provides a sodium-potassium co-doped lithium-ion battery cathode material prepared by the aforementioned preparation method.
[0044] In some embodiments, the sodium-potassium co-doped lithium-ion battery cathode material has a composition of Li. 0.997 K 0.003-x Na x Ni 0.83 Co 0.12 Mn 0.05 O2, where x takes the value 0. <x<0.003。
[0045] In some embodiments, the sodium-potassium co-doped lithium-ion battery cathode material is in the form of smooth granules with a particle diameter of 3-5 micrometers. The sodium-potassium co-doped lithium-ion battery cathode material of the present invention is a secondary particle formed by the aggregation of primary particles, with a smooth particle surface and less surface residual alkali compared to the undoped sample.
[0046] A third aspect of the present invention provides a lithium-ion cathode comprising the sodium-potassium co-doped lithium-ion battery cathode material.
[0047] A fourth aspect of the present invention provides a lithium-ion battery comprising a negative electrode, a positive electrode, and an electrolyte, wherein the positive electrode comprises the lithium-ion positive electrode.
[0048] In some implementations, the lithium-ion battery retains more than 80% of its capacity after 170 cycles at 1C and more than 81% of its capacity after 200 cycles at 5C.
[0049] In some embodiments, the lithium-ion diffusion coefficient (LgD) of the lithium-ion battery is -9.5 to -10.8.
[0050] In some implementations, the lithium-ion battery includes a lithium-ion coin cell.
[0051] In summary, this invention utilizes a sodium-potassium co-doping strategy to prepare Li 0.997 K 0.003- x Na x Ni 0.83 Co 0.12 Mn 0.05 O2 (NCM-NK) materials achieved synergistic optimization of bulk dynamics and structural stability, Na + Doping can stabilize Li + Coordination environment, suppressing H2-H3 phase transformation stress; K + Doping can increase the interlayer spacing and reduce Li + The migration energy barrier enhances the intrinsic diffusion rate. Sodium-potassium co-doped NCM-NK materials exhibit superior long-cycle performance.
[0052] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Modifications or equivalent substitutions made by those skilled in the art based on their understanding of the technical solutions of this invention, without departing from the spirit and scope of the invention, should be covered within the protection scope of this invention.
[0053] For experiments not specifically described in the examples, the procedures or conditions can be performed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available. Other unmentioned raw materials and instruments are all conventionally chosen and do not involve the core technical means of this invention.
[0054] Example 1
[0055] Ni 0.83 Mn 0.12 Co 0.05(OH)₂ and LiOH·H₂O were mixed at a molar ratio of 1:1.02. CH₃COONa·H₂O and KNO₃ were added as dopants, with a Na to K molar ratio of 1:2. The mixture was thoroughly ground and then placed in an alumina crucible for heat treatment in a tube furnace under an oxygen atmosphere. The sintering conditions were 560℃ preheating for 3 hours and 800℃ calcination for 12 hours, ultimately yielding a K and Na co-doped NCM811 sample, denoted as K₂Na₁-NCM811. The SEM image at 30 μm is shown below. Figure 1a As shown, the material exhibits a uniform morphology, exhibiting a secondary particle aggregate formed from primary particle aggregation; the SEM image at 2 μm is shown below. Figure 1b As shown, the material surface is smooth and has little residual alkali.
[0056] K2Na1-NCM811 was assembled into a coin cell and its electrochemical performance was tested. Under charge-discharge conditions of 25℃, 0.1C, and 2.8-4.3V, the material's initial discharge capacity at 0.1C reached 202 mAh / g. The test results are as follows: Figure 5 As shown.
[0057] After 170 cycles at 1C (1C = 180mAh / g), the capacity retention rate reached 80.32%, as shown in the test results. Figure 6 As shown in the figure. After 200 cycles at a 5C rate, the capacity retention reached 86.3%, as shown in the test results. Figure 7 As shown, the initial discharge capacity during long-cycle operation at 1C and 5C rates reached 182.5 mAh / g and 153.4 mAh / g, respectively.
[0058] Cyclic voltammetry (CV) results show that K2Na1-NCM811 exhibits minimal polarization, as shown in the test results below. Figure 8 As shown in the figure. Intermittent galvanostatic titration (GITT) test data confirms that its lithium-ion diffusion coefficient is significantly improved compared to the undoped material P-NCM811, as shown in the test results. Figure 9 As shown. XRD characterization is as follows. Figure 10 As shown.
[0059] The electrochemical performance test results of K2Na1-NCM811 in this embodiment are shown in Table 1.
[0060] Example 2
[0061] Ni 0.83 Mn 0.12 Co 0.05(OH)₂ and LiOH·H₂O were mixed at a molar ratio of 1:1.02. CH₃COONa·H₂O and KNO₃ were added as dopants, with a Na to K molar ratio of 2:1. The mixture was thoroughly ground and then placed in an alumina crucible for heat treatment in a tube furnace under an oxygen atmosphere. The sintering conditions were 560℃ preheating for 3 hours and 800℃ calcination for 12 hours, ultimately yielding a K and Na co-doped NCM811 sample, denoted as K1Na₂-NCM811. The SEM image at 30 μm is shown below. Figure 2a As shown, the SEM image at 2μm is as follows Figure 2b As shown.
[0062] K1Na2-NCM811 was assembled into a coin cell and its electrochemical performance was tested. Under charge-discharge conditions of 25℃, 0.1C, and 2.8-4.3V, the material's initial discharge capacity at 0.1C reached 210.5 mAh / g. The test results are as follows: Figure 5 As shown in the figure. After 170 cycles at 1C (1C = 180mAh / g), the capacity retention rate reached 86.9%, as shown in the test results. Figure 6 As shown in the figure. After 200 cycles at a 5C rate, the capacity retention reached 81.2%, as shown in the test results. Figure 7 As shown, the initial discharge capacity during long-cycle operation at 1C and 5C rates reached 184.2 mAh / g and 164.1 mAh / g, respectively.
[0063] Cyclic voltammetry (CV) results showed that the third oxidation peak in the first cycle of K1Na2-NCM811 was significantly reduced, indicating that the H2-H3 phase transition was stabilized on the surface. The test results are as follows: Figure 8 As shown in the figure; the intermittent titration (GITT) test data confirms that its lithium-ion diffusion coefficient is significantly improved compared with the undoped material P-NCM811 and the single-doped K material. The test results are as follows. Figure 9 As shown. XRD characterization is as follows. Figure 10 As shown.
[0064] The electrochemical performance test results of K1Na2-NCM811 in this embodiment are shown in Table 1.
[0065] Comparative Example 1
[0066] Ni 0.83 Mn 0.12 Co 0.05(OH)₂ and LiOH·H₂O were mixed at a molar ratio of 1:1.02, and KNO₃ equivalent to 0.3 mol% of the total cations was added. The mixture was thoroughly ground and then placed in an alumina crucible for heat treatment in a tube furnace under an oxygen atmosphere. First, it was pre-calcined at 560℃ for 3 hours, followed by calcination at 800℃ for 12 hours. The sample was then allowed to cool naturally to room temperature with the furnace and was designated K₃Na₀-NCM₈11. The SEM image at 30 μm is shown below. Figure 3a As shown, the SEM image at 2μm is as follows Figure 3b As shown.
[0067] K3Na0-NCM811 was assembled into a coin cell and its electrochemical performance was tested. Under charge-discharge conditions of 25℃, 0.1C, and 2.8-4.3V, the initial discharge capacity of the material reached 222.5 mAh / g. The test results are as follows: Figure 5 As shown.
[0068] After 170 cycles at 1C (1C = 180mAh / g), the capacity retention rate reached 88.36%, as shown in the test results. Figure 6 As shown; after 200 cycles at a 5C rate, the capacity retention rate reached 78.11%, as the test results are shown below. Figure 7 As shown, the initial discharge capacity during long-cycle operation at 1C and 5C rates reached 204.5 mAh / g and 195.1 mAh / g, respectively.
[0069] Cyclic voltammetry (CV) results show that K3Na0-NCM811 has small polarization, as shown in the test results. Figure 8 As shown in the figure; intermittent galvanostatic titration (GITT) test data confirms that its lithium-ion diffusion coefficient is significantly improved compared with the undoped material P-NCM811, as shown in the test results. Figure 9 As shown. XRD characterization is as follows. Figure 10 As shown.
[0070] The electrochemical performance test results of K3Na0-NCM811 in this comparative example are shown in Table 1.
[0071] Comparative Example 2
[0072] Ni 0.83 Mn 0.12 Co 0.05 (OH)₂ and LiOH·H₂O were mixed at a molar ratio of 1:1.05. After grinding the mixture evenly, it was placed in an alumina crucible and heat-treated in a tube furnace under an oxygen atmosphere: first, pre-calcination was carried out at 560℃ for 3 hours, followed by calcination at 800℃ for 12 hours. The sample was then allowed to cool naturally to room temperature in the furnace to obtain an undoped blank sample P-NCM811. The SEM image at 30 μm is shown below. Figure 4aAs shown, the SEM image at 2μm is as follows Figure 4b As shown.
[0073] P-NCM811 was assembled into a coin cell and its electrochemical performance was tested. Under charge-discharge conditions of 25℃, 0.1C, and 2.8-4.3V, the material's initial discharge capacity at 0.1C reached 195.5 mAh / g. The test results are as follows: Figure 5 As shown in the figure. After 170 cycles at 1C (1C = 180mAh / g), the capacity retention rate reached 79.6%, as shown in the test results. Figure 6 As shown in the figure. After 200 cycles at a 5C rate, the capacity retention rate was 80.57%, as shown in the test results. Figure 7 As shown, the initial discharge capacity during long-cycle operation at 1C and 5C rates reached 177.5 mAh / g and 148.3 mAh / g, respectively.
[0074] Cyclic voltammetry (CV) test results are as follows Figure 8 As shown, the test results of the galvanostatic intermittent titration technique (GITT) are as follows: Figure 9 As shown, the XRD characterization is as follows Figure 10 As shown.
[0075] The electrochemical performance test results of P-NCM811 in this comparative example are shown in Table 1.
[0076] In this invention, according to Figure 5 As shown, compared with the blank sample P-NCM811, the double-doped cathode materials all show improved rate performance; K2Na1-NCM811 and K1Na2-NCM811 have a lower specific capacity than K3Na0-NCM811, but they have a significant improvement in subsequent 5C high-rate long-cycle performance.
[0077] according to Figure 6 and Figure 7 As shown, with the increase of sodium ratio in the double-doped cathode material, the long cycle retention rate at 1C rate decreases, but the long cycle retention rate at 5C rate increases significantly.
[0078] according to Figure 8 As shown, the increased sodium content in the double-doped cathode material inhibits the H2-H3 phase transition.
[0079] according to Figure 9 As shown, the diffusion coefficients of all lithium ions in the double-doped cathode material are improved. The highest lithium ion diffusion coefficient is achieved when the sodium ratio is K1Na2-NCM811, which is due to the promotion of lithium ion diffusion by the dual-pillar effect.
[0080] Table 1. Electrochemical performance test results of samples obtained in Examples 1-2 and Comparative Examples 1-2
[0081]
[0082] Therefore, the present invention can achieve a dual-pillar effect by introducing sodium ion doping on the basis of potassium doping. Although the capacity is lower than that of single K doping, the introduction of Na improves the cycle retention rate and ion diffusion coefficient at high rates and effectively reduces the H2-H3 phase transition.
[0083] All aspects, embodiments, features, and examples of this invention should be considered illustrative in all respects and are not intended to limit the invention; the scope of the invention is defined only by the claims. Other embodiments, modifications, and uses will become apparent to those skilled in the art without departing from the spirit and scope of the invention.
[0084] In addition, the inventors of this case also conducted experiments with other raw materials, process operations, and process conditions described in this specification, referring to the aforementioned embodiments, and obtained relatively ideal results in all cases.
[0085] Although the invention has been described with reference to illustrative embodiments, those skilled in the art will understand that various other changes, omissions, and / or additions can be made without departing from the spirit and scope of the invention, and that elements of the described embodiments can be substituted with substantially equivalents. Furthermore, many modifications can be made without departing from the scope of the invention to adapt particular situations or materials to the teachings of the invention. Therefore, this invention is not intended to be limited to the specific embodiments disclosed for carrying out the invention, but rather is intended to encompass all embodiments falling within the scope of the appended claims.
Claims
1. A method for preparing a sodium-potassium co-doped lithium-ion battery cathode material, characterized in that, include: Ni 0.83 Mn 0.12 Co 0.05 The (OH)2 precursor was mixed evenly with the lithiation agent, and sodium and potassium salts were added as dopants. Then, the mixture was pre-calcined and calcined in an oxygen atmosphere to obtain sodium-potassium co-doped lithium-ion battery cathode material.
2. The preparation method according to claim 1, characterized in that, The preparation method specifically includes: pre-calcining at 480-560℃ for 2-4 hours, followed by calcination at 780-810℃ for 10-14 hours to obtain the sodium-potassium co-doped lithium-ion battery cathode material.
3. The preparation method according to claim 1, characterized in that: The molar ratio of sodium in the sodium salt to potassium in the potassium salt is 1:2 to 2:
1. And / or, the Ni 0.83 Mn 0.12 Co 0.05 The molar ratio of (OH)2 precursor to LiOH·H2O is 1:1.04~1.6; And / or, the Ni 0.83 Mn 0.12 Co 0.05 The molar ratio of (OH)2 precursor to dopant is 1:0.003; And / or, the Ni 0.83 Mn 0.12 Co 0.05 The (OH)2 precursor was prepared by a ternary coprecipitation method.
4. The preparation method according to claim 1, characterized in that: The lithium-forming agent includes LiOH·H2O; And / or, the sodium salt includes CH3COON a H2O; And / or, the potassium salt includes KNO3.
5. A sodium-potassium co-doped lithium-ion battery cathode material prepared by any one of claims 1-4.
6. The sodium-potassium co-doped lithium-ion battery cathode material according to claim 5, characterized in that: The sodium-potassium co-doped lithium-ion battery cathode material has the following composition: Li 0.997 K 0.003-x Na x Ni 0.83 Co 0.12 Mn 0.05 O2, where x takes the value 0 < x < 0.
003.
7. The sodium-potassium co-doped lithium-ion battery cathode material according to claim 5, characterized in that: The sodium-potassium co-doped lithium-ion battery cathode material is in the form of smooth granules with a particle diameter of 3-5 μm.
8. A lithium-ion cathode, characterized in that, The lithium-ion battery cathode material including any one of claims 5-7, which is co-doped with sodium and potassium.
9. A lithium-ion battery, comprising a negative electrode, a positive electrode, and an electrolyte, characterized in that: The positive electrode includes the lithium-ion positive electrode as described in claim 8.
10. The lithium-ion battery according to claim 9, characterized in that: The lithium-ion battery retains more than 80% of its capacity after 170 cycles at 1C rate and more than 81% of its capacity after 200 cycles at 5C rate. And / or, the lithium-ion diffusion coefficient lgD of the lithium-ion battery is -9.5 to -10.8; And / or, the lithium-ion battery includes a lithium-ion coin cell.
